Inclusion of buffalo milk artisan yogurt in the feed for Iaying hens Isa Brown and its effect on egg production and quality - Ortiz-Milán, Abel; Gómez-Sarabia, Solimar; Jay-Herrera, Osmany; Brea-Maura, Odelin (Ciencia y Agricultura, 2017)
A total of 240 birds were used in the state of Delta Amacuro, Venezuela, for 60 days in order to assess the inclusion of 0 (control), 5, 10 and 15 ml of anisan yogurt / bird / day in the feed for laying hens Isa Brown, and its effect on egg production and quality, according to completely randomized design with four treatments and six repetitions, each repetition consisted of 10 hens. At the end of the experiment it was found that the total egg production (3.04, 3.22, 3.38 and 3.58 kg/bird), the laying rate (88,66, 90.00, 93.33 and 96.66 %), conversion (2.37, 2.24, 2.13 and 2.01 kg feed/kg eggs) and egg weight (58.96, 60.86, 62.33 and 65.26 g) improved significantly in birds to the extent that it was increased on feed the buffalo yogurt dose. The percentage of broken eggs did not differ between treatments, while in the percentage of eggs hulled and dirty eggs was significantly superior for 15 ml of yogurt with respect control. The sensory characteristics of cooked egg (smell, taste and texture) showed no significant changes according to pane|ists’ criteria. It is concluded that the inclusion of artisan yogurt made from buffalo milk in the diet for laying hens Isa Brown stimulated laying rate and egg size without significant effects in the sensory quality of the egg.